1982
DOI: 10.1007/bf00014959
|View full text |Cite
|
Sign up to set email alerts
|

Facteurs influen�ant la structure des groupements de macro-invert�br�s benthiques et phytophiles dans la zone littorale du Saint-Laurent (Qu�bec)

Abstract: In the littoral zone of the St-Lawrence River (Quebec, Canada), benthic and phytophilous macroinvertebrates were studied in order to find and to explain relationships between structure of these animal communities and abiotic (substrate, water depth, current velocity) or biotic (marophytes species) factors . Benthos was sampled at 16 sites in spring, when there was no macrophytic vegetation, and in summer . Phytomacrofauna was sampled at 30 sites in summer . The data were analyzed using simple and partial corre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
11
1
1

Year Published

1986
1986
2008
2008

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 21 publications
3
11
1
1
Order By: Relevance
“…m -2 in the 0 -3 cm layer). This is in contrast with many findings in the literature, according to which the macro-invertebrate density is normally much higher in macrophyte stands than in the sediments (Gerking 1957;Pieczynski 1973;Soszka 1975;Vincent et al 1982;Rasmussen 1988). The community structure in the reference sites was dominated by ostracods, mussels (mainly Dreissena polymorpha), chironomid larvae and mayfly larvae which have been proved to be among the most frequent taxonomic groups in many other lentic lake shore habitats.…”
Section: Discussioncontrasting
confidence: 86%
“…m -2 in the 0 -3 cm layer). This is in contrast with many findings in the literature, according to which the macro-invertebrate density is normally much higher in macrophyte stands than in the sediments (Gerking 1957;Pieczynski 1973;Soszka 1975;Vincent et al 1982;Rasmussen 1988). The community structure in the reference sites was dominated by ostracods, mussels (mainly Dreissena polymorpha), chironomid larvae and mayfly larvae which have been proved to be among the most frequent taxonomic groups in many other lentic lake shore habitats.…”
Section: Discussioncontrasting
confidence: 86%
“…Vicent et al (1982) observed that the fauna in the macrophytes presents a magnitude of two to three times the abundance of zoobenthos in the litoral zone.…”
Section: Introductionmentioning
confidence: 99%
“…This technique, was adopted after comparison with that used by Mackie & Quadri (1971) and by Vincent et al (1982) . It is well adapted to a single sampling of the epiphytic gastropods, to the muddy sediment, the size of the macrophytes and the shallow depth .…”
Section: Sampling Designmentioning
confidence: 99%
“…Lawrence River, the littoral zone covers large surfaces and is colonized in summer by numerous macrophytes that support a very abundant and diverse fauna dominated by gastropods (Vincent et al, 1982). Lawrence River, the littoral zone covers large surfaces and is colonized in summer by numerous macrophytes that support a very abundant and diverse fauna dominated by gastropods (Vincent et al, 1982).…”
Section: Introductionmentioning
confidence: 99%